Outcomes of acute kidney injury in critically ill children who need renal replacement therapy - Danka Pokrajac; Admir Hadžimuratović; Ismeta Kalkan; Nedim Begić; Emina Hadžimuratović; Verica Mišanović; Duško Anić; Aida Mustajbegović-Pripoljac (Medicinski glasnik, 2022)
Aim: To determine an outcome of acute kidney injury (AKI) in critically ill children (CIC) who needed renal replacement therapy (RRT) and were admitted to the Paediatric and Neonatal Intensive Care Unit (PICU and NICU) at the Paediatric Clinic, University Clinical Centre Sarajevo (UCCS). Methods: The research included 81 children with AKI. The Kidney Disease: Improving Global Outcomes (KDIGO) criteria to define AKI was used. Other laboratory findings and imaging tests were made depending on children’s primary disease that led to the AKI. Results: Among 81 children with AKI, 38 were girls and 43 boys. A total of 39 (48.1%) patients died; the death was due to the nature of the primary disease and multiple organ failure syndromes. Out of the total of 81 patients the highest mortality rate was found in children in the first year of life, 22 (56.4%), while 17 (43.6%) patients died after the first year of life. Conclusion: Without an accurate diagnosis at the right time, due to the lack of adequate biomarkers for AKI screening, the heterogeneity of AKI, comorbidities often lead to unfavourable outcomes of the disease, among CIC, especially in infants with low birth weight and extreme immaturity. Some causes of AKI are preventable and can be reduced by a better organization of primary and secondary health care.
Keywords: dialysis; morbidity; mortality